PENGARUH BEBERAPA PROSES PENGOLAHAN DAN LAMA PENYIMPANAN PAKAN IKAN YANG DITAMBAHKAN PEREKAT TAPIOKA TERHADAP BEBERAPAUJI SIFAT FISIK RANSUM - Y. Retnani; L. Herawati; N. R. Desriani (Jurnal Peternakan, 2010)
The purpose this study was to ktww the influence ofseveral processing and the storage periods offish ration added with tapioca binder on the physical characteristics offish ration. This research used a 3 x 4factorial completely randomized design with 3 replications. The data were analyzed by analysis ofvariance and the significant result would be examined by orthogonal contrast test. Factor A was processing (without treatment, AD); spraying with 5% hot water (AI) and steamingfor 45 minutes (A2), while factor B was storage periods(O, 2, 4, and 6 weeks). The parameters investigated were water activity, water content, particle size, .pellet durability, loose bulk density and compressed bulk density. The results showed that processing without treatment, spraying with 5% hot water and steaming for 45 minutes did not affect the physical characteristics of ration. However, the water content and particle size of the ration were significantly affected by processing treatments (p<O.Ol). The water content was 13.69%, 13.71% and 14.42%, while particle size of the ration processing without treatment, spraying with 5 % and spraying with 5% hot water were 0.659 em, 0.652 em and 0.658 em, repectively. The storage period highly significant influenced (p<O.Ol) physical characteristics of the ration, the value ofwater activity atoweek to 6 weeks storage periods were 0.83, 0.78, 0.76 and 0.76; water content were 14.34%, 14.82%, 13.30% and 13.30%; particle size were 0.663 em, 0.659 em, 0.651 em and 0.651 em; pellet durability were 99.95%, 99.79%, 99.73% and 99.57%; loose bulk density were 0.639 g/em3, 0.543 g/em3, 0.534 g/em3 and 0.50p g/em3; and compressed bulk density were 0.691 g/em3, 0.630 g/em3, 0.718 g/em3 and 0.712 g/em3, respectively. The results indicated that storage period decreased the physical characteristics of ration. In conclusion, the best quality offish ration was ration processed by spraying with 5% hot water and 4 weeks storage.